2019
DOI: 10.1177/2378023119872387
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Assessments of Gender Equality

Abstract: Women’s assessments of gender equality do not consistently match global indices of gender inequality. In surveys covering 150 countries, women in societies rated gender-unequal according to global metrics such as education, health, labor-force participation, and political representation did not consistently assess their lives as less in their control or less satisfying than men did. Women in these societies were as likely as women in index-equal societies to say they had equal rights with men. Their attitudes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 45 publications
1
11
0
4
Order By: Relevance
“…Without FIML, the common default of listwise deletion in Model 1 (n = 113) excluded three OECD countries and 38 countries with populations of over one million, which is normal with the common criteria used for sample selection in the quantitative literature (see Appendix B). To be clear, in the social sciences, generally, the issue of missing data continues to be handled by way of listwise deletion or largely ignored, even in studies published in social science journals with an explicit focus on innovative empirical research [46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…Without FIML, the common default of listwise deletion in Model 1 (n = 113) excluded three OECD countries and 38 countries with populations of over one million, which is normal with the common criteria used for sample selection in the quantitative literature (see Appendix B). To be clear, in the social sciences, generally, the issue of missing data continues to be handled by way of listwise deletion or largely ignored, even in studies published in social science journals with an explicit focus on innovative empirical research [46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…Based on these ques tions, we cre ate indi ca tor var i ables sep a rately for hus bands and wives, coded as 1 if a hus band/wife rejects wife beat ing (i.e., reports that it is not justi fied across all five sce nar ios) and 0 if the hus band/wife accepts wife beat ing (i.e., reports that it is jus ti fied for one or more sce nario). Consistent with the lit er a ture, we refer to rejec tion of wife beat ing as "rejec tion of IPV" even though it refers to only one form of IPV (i.e., phys i cal vio lence) across five spe cific sce nar ios (for a sim i lar approach, see Cools and Kotsadam 2017;Kurzman et al 2019;Pierotti 2013;Uthman et al 2009). 4 Based on these indi vid ual-level binary indi ca tors of IPV rejec tion, we cre ate a cat e gor i cal var i able that con sid ers the hus band-wife responses jointly (1) concor dance in rejecting IPV across all sce nar ios; (2) dis cor dance in which the hus band, but not the wife, rejects IPV across all sce nar ios; (3) dis cor dance in which the wife, but 4 In our sam ple, 2,452 wives and 1,157 hus bands reported that they do not know whether wife beat ing is jus ti fied for at least one of the sce nar ios; respon dents who reported that they "do not know" whether wife beat ing is jus ti fied are coded as 0 for that sce nario.…”
Section: Concordance and Discordance In Husband/wife Rejection Of Ipvmentioning
confidence: 99%
“…30 There is an extensive literature which suggests that educated women are more likely to adopt new technologies such as modern contraceptives and lifestyles which in due course diffuse to the new cohorts of women. 31 , 32 We characterize our target population as an innovative group. Focus on this target population provides us an opportunity to explore the impact of reproductive rights knowledge on contraceptive use in an innovative group.…”
Section: Methodsmentioning
confidence: 99%